1997
DOI: 10.1006/viro.1997.8691
|View full text |Cite
|
Sign up to set email alerts
|

Field and Vaccine Strains of Fowlpox Virus Carry Integrated Sequences from the Avian Retrovirus, Reticuloendotheliosis Virus

Abstract: For baculoviruses and herpesviruses, integration of transposons or retroviruses into the virus genome has been documented. We report here that field and vaccine strains of fowlpox virus (FPV) carry integrated sequences from the avian retrovirus, reticuloendotheliosis virus (REV). Using PCR and hybridization analysis we observed that vaccine and field strains of FPV carry REV sequences integrated into a previously uncharacterized region of the right 1/3 of the FPV genome. Long-range PCR, hybridization, and nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
120
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 17 publications
7
120
1
2
Order By: Relevance
“…Previously published reports indicate dual or coinfections of herpesvirus and retrovirus can occur within a single host (Pietroboni et al, 1988;Heng et al, 1994;Davidson et al, 2002), resulting in insertion of retrovirus sequences into the genome of herpesvirus (Isfort et al, 1992(Isfort et al, , 1994bKost et al, 1993;Sakaguchi et al, 1997). Recombination occurs both in vitro following co-infection of cell culture and naturally in vivo following mixed infection of avian species with DNA and RNA viruses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously published reports indicate dual or coinfections of herpesvirus and retrovirus can occur within a single host (Pietroboni et al, 1988;Heng et al, 1994;Davidson et al, 2002), resulting in insertion of retrovirus sequences into the genome of herpesvirus (Isfort et al, 1992(Isfort et al, , 1994bKost et al, 1993;Sakaguchi et al, 1997). Recombination occurs both in vitro following co-infection of cell culture and naturally in vivo following mixed infection of avian species with DNA and RNA viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination occurs both in vitro following co-infection of cell culture and naturally in vivo following mixed infection of avian species with DNA and RNA viruses. Integration of a REV long terminal repeat (LTR) into fowlpoxvirus in avian species demonstrated that natural recombination occurs in nature and can lead to unexpected changes in the retroviral spread pattern and pathogenicity of the resultant recombinant virus (Hertig et al, 1997). Furthermore, beginning in 1993, an extensive survey of Israeli commercial flocks evaluated the incidence and the prevalence of flocks and birds with multiple viral infections (Davidson et al, 1995;Davidson & Borenshtain, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission of REV via contaminated fowlpox vaccines has been documented in turkeys and chickens (Fadly et al, 1996;Fadley and Witter, 1997). Field and vaccine strains of fowlpox viruses from Australia, Europe, and the United States have been shown to carry sequences of the REV genome integrated into the fowlpox virus DNA (Hertig et al, 1997). Some pox viruses carry near full-length REV provirus sequences which can generate fully infectious virions when the contaminated pox virus is injected into susceptible chickens.…”
mentioning
confidence: 99%